CPR: Bright side of machine-human relationship - Shaik Farid Abdull Wahab; Ahmad Rasdan Ismail; Rohayu Othman (2018)
Cardio pulmonary resuscitation (CPR) is a common procedure at Accident and Emergency Department, especially in the Red Zone or Resuscitation Room. This procedure is done as a method to save patients’ life, especially in the event of cardiac arrest. Medical doctors or nurses do continuous cycles of chest compressions manually in order to ensure the heart keep pumping. This is vital in making sure blood supply to the heart and brain is not interrupted. The external force needed to compress the chest is a result of continuous pressing of the heart at the level of mid chest. One cannot deny, the process can be exhausting and can cause muscular pain to the medical doctors or nurses. However, with innovation and technology, nowadays, CPR can be done using machine. The objective of this study is to justify how the relationship of human and machine, has not only save patients life, but also able to safe the medical doctors and nurses from the risk of musculoskeletal disorder (MSD). This study has been carried out at Red Zone of Accident and Emergency Department, Hospital Universiti Sains Malaysia, Kota Bharu, Kelantan, Malaysia. During this study, 10 medical doctors participated. 8 females and 2 male doctors were voluntarily involved in this study. All of them were asked to perform CPR while standing on the floor and while standing on a stool and patient lying on the bed. Their body postures were recorded and score were given based on Rapid Entire Body Assessment (REBA). This score will determine whether they might have the risk of MSD due to performing CPR or not. For this study, a mannequin was used instead of real patient. Two mechanical CPR device machines were selected in this study, which were LUCAS and AutoPULSE. CPR by these machines was also performed on the mannequin. Result showed, REBA scores are high risk and very high risk. The REBA score when performing CPR while standing on stool were higher compared to REBA score when performing CPR while standing on the floor. Thus, the existing machine-like LUCAS and AutoPULSE in doing CPR not only save patients life, but also have helped the medical doctors and nurses as well. The teaming between machine and human in this study has proven to bring benefits to human life, especially to the medical doctors and nurses.